3D-printed porous tantalum: recent application in various drug delivery systems to repair hard tissue defects. (4th May 2021) - Hua, Long; Lei, Ting; Qian, Hu; Zhang, Yu; Hu, Yihe; Lei, Pengfei
ABSTRACT: Introduction: The treatment of hard tissue defects, especially those of bone and cartilage, induced by infections or tumors remains challenging. Traditional methods, including debridement with systematic chemotherapy, have shortcomings owing to their inability to eliminate infections and high systematic toxicity. Area covered: This review comprehensively summarizes and discusses the current applications of 3D-printed porous tantalum (3D-P-p-Ta), a novel drug delivery strategy, in drug delivery systems to repair hard tissue defects, as well as the limitations of existing data and potential future research directions. Expert opinion: Drug delivery systems have advanced medical treatments, with the advantages of high local drug concentration, long drug-release period, and minimal systematic toxicity. Due to its excellent biocompatibility, ideal mechanical property, and anti-corrosion ability, porous tantalum is one of the most preferable loading scaffolds. 3D printing allows for freedom of design and facilitates the production of regular porous implants with high repeatability. There are several reports on the application of 3D-P-p-Ta in drug delivery systems for the management of infection- or tumor-associated bone defects, yet, to the best of our knowledge, no reviews have summarized the current research progress.